Acceptance and Commitment Therapy and Multiple Sclerosis: analysis of the film 100 meters - Formiga, Mariana Bandeira; Aguirre, Jorge Luis Quintero (Perspectivas em Análise do Comportamento, 2025)
This article aims to analyze the film “100 meters” using the Hexaflex perspective of psychological flexibility and inflexibility of Acceptance and Commitment Therapy (ACT). T he analysis of the film followed the chronological order in which the protagonist’s scenes are displayed. These were enumerated, identified in relation to the time in which they appear, described and commented based on the ACT processes. The six ACT processes of psychological flexibility and inflexibility were identified in the protagonist’s scenes. It is considered that this study can be used as an instrument to understand ACT by illustrating the processes of this approach, as well as by demonstrating how the processes are intertwined in the analysis, corroborating that its division is mainly didactic.